Salt Water Irrigation Frequency for Barley - Kirkham, M B (Annals of Arid Zone, 2016)
Barley ( Hordeum vulgare L. ’Liberty’), grown in pot (28 cm diameter; 28 cm height) sand culture in greenhouse, was irrigated at four different rates with water containing three different concentrations of NaCl (0, 10,500 and 23,000 ppm) to determine an optimum irrigation frequency for salt water tolerant varieties of barley which yield fairly well on coastal sandy areas. Beginning 14 days after planting, solutions were applied periodically to each pot, but at four different frequencies : 250 ml daily, 1000 ml every 4 days, 2000 ml every 8. days, and 3000 ml every 12 days. The’ more frequently barley in sand was irrigated with salt water, the higher was the grain yield. The results suggested that new sea water tolerant varieties of barley how being developed must be irrigated frequently (daily) with salt water to maintain sufficient moisture in the root zone of coastal sands for growth to occur.